Borges : form and the sublime. - Chia, Ying Mei. (2009)
Reading and writing about Jorge Luis Borges can be challenging, as his work reflects his vast knowledge of literature, philosophy, mathematics, and even, to a certain extent, physics. He also displays a wide range of writing styles that defy neat classification into genres. This essay attempts to find out what Borges is seeking through his writing, because it is blatantly obvious that there is a huge driving force behind the exploratory bent in his work, and argues that his writing functions as a record of his intellectual exploration. His use of various narrative strategies creates complex works that mirror his perception of the labyrinthian universe, and his writing serves as a way of framing and accessing the sublime. Borges’ writing also shows that he never manages to understand the universe and how it works, because the universe as he sees it is ineffable and impossible for a human to fully understand. Although his work sometimes reveals how intimidating this complexity is, it is by and large a celebration of the strangeness of the sublime in the universe, and Borges is comfortable with this strangeness, because he knows that "in this world, beauty is of all of us" (Poems 267) and that is meaning enough for him.